The book of Daniel : composition and reception - Flint, Peter W.; Collins, John J. 1946- (Vetus Testamentum, Supplements, 2001)
In this collection of new essays, more than thirty leading scholars from Europe, North America and Israel examine the Composition and Reception of Daniel in eight sections: Review of Scholarship and Context (J.J. Collins, M. Knibb); Near Eastern Milieu (K. van der Toorn, S. Paul, J. Walton); Interpretation of Specific Passages (D. Dimant, R. Kratz, A. Lacocque, E. Haag, J.-W. van Henten); Social Setting (R. Albertz, S. Beyerle, L. Grabbe, P. Davies, D. Smith-Christopher); Literary Context, including Qumran (J.-W. Wesselius, G. Boccaccini, P.W. Flint, L. Stuckenbruck, E. Eshel, J. Hobbins); Reception in Judaism and Christianity (K. Koch, C. Rowland, U. Gleßmer, C.A. Evans, J.D.G. Dunn, M. Henze); Textual History (E. Ulrich, A.A. Di Lella, K. Jenner) and Theology of Daniel (J. Goldingay, J. Barton, J. Lust). This is the second volume to appear (following Writing and Reading the Scroll of Isaiah. Studies of an Interpretative Tradition ) in the collection The Formation and Interpretation of Old Testament Literature , part of the series Supplements to Vetus Testamentum . Further volumes in preparation on the composition and reception of Old Testament books include Genesis, Leviticus, Kings, Psalms, and Proverbs. This publication has also been published in paperback, please click here for details.